Methionine and Glycine Stabilize Mitochondrial Activity in Sake Yeast During Ethanol Fermentation - Kusaba, Yuki; Fujimaru, Yuki; Yamamoto, Yuki; Kitagaki, Hiroshi; Jannatul, Ferdouse (Food technology and biotechnology, 2019)
Addition of amino acids to fermentation media affects the growth and brewing profiles of yeast. In addition, retaining mitochondrial activity during fermentation is critical for the fermentation profiles of brewer’s yeasts. However, a concrete mechanism linking amino acids in fermentation media with mitochondrial activity during fermentation of brewer’s yeasts is yet unknown. Here, we report that amino acids in fermentation media, especially methionine (Met) and glycine (Gly), stabilize mitochondrial activity during fermentation of sake yeast. By utilizing atg32Δ mutant sake yeast, which shows deteriorated mitochondrial activity, we screened candidate amino acids that strengthened the mitochondrial activity of sake yeast during fermentation. We identified Met and Gly as candidate amino acids that fortify mitochondrial activity in sake yeast during fermentation. To confirm this biochemically, we measured reactive oxygen species (ROS) levels in sake yeast fermented with Met and Gly. Yeast cells supplemented with Met and Gly retained high ROS levels relative to the non-supplemented sake yeast. Moreover, Met-supplemented cells showed a metabolome distinct from that of non-supplemented cells. These results indicate that specific amino acids such as Met and Gly stabilize the mitochondrial activity of sake yeast during fermentation and thus manipulate brewing profiles of yeast.